Evaluation to Perform a Scattered for Detecting Selfish Nodes in MANET using Collabrative Watchdog Algorithm - Manikandan, R; Mangayarkarasi, R (International Journal of Computer Sciences and Engineering, 2019)
A mobile ad hoc network (MANET) is a self-organized system comprised by multiple mobile wireless nodes. The node misbehavior due to selfish reasons can significantly diminish the performance of MANET. A selfish node attempts to use the resources only for its own purpose and it hesitates to share the resources with their neighbors. So, it is very important to detect the selfish nodes to improve the performance of MANET. Initially, an architectural model of a MANET is constructed and the communication between the mobile is originated. The packet drop can happen in MANET due to the selfish node or network congestion. In this paper, a distributed global trust is presented to improvise the detection of selfish node in the network in MANET and then This paper studies the impact of selfish nodes concentration on the quality of service in MANETs. The main reason for using trust and reputation in this analysis is to accelerate the detection of misbehaving nodes. This study has been carried out in order to analyze the detection of selfish nodes on essential network functions such as routing and packet dropping. The simulation study demonstrate the proposed method enhances the selfish node detection ratio , packet delivery ratio(PDR), and average packet drop ratio, Quality of service.